2014
DOI: 10.1080/10402004.2014.937886
|View full text |Cite
|
Sign up to set email alerts
|

Lubricating Grease Shear Flow and Boundary Layers in a Concentric Cylinder Configuration

Abstract: Grease is extensively used to lubricate various machine elements such as rolling bearings, seals, and gears. Understanding the flow dynamics of grease is relevant for the prediction of the grease distribution for optimum lubrication and the migration of wear-and contaminant particles. In this study grease flow is visualized using the method of micro Particle Image Velocimetry; the experimental setup comprises a concentric cylinder with rotating shaft to simulate the grease flow in a Double Restriction Seal (DR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
1
20
0
Order By: Relevance
“…Wall slip is for instance not considered in rheometers and the grease is assumed to be uniformly sheared throughout the gap. A couple of papers by the authors have shown that these conditions in fact are violated for the case of grease flow [29,18]. A consequence of this is the question how reliable the values from a rheometer are in terms of grease rheology.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Wall slip is for instance not considered in rheometers and the grease is assumed to be uniformly sheared throughout the gap. A couple of papers by the authors have shown that these conditions in fact are violated for the case of grease flow [29,18]. A consequence of this is the question how reliable the values from a rheometer are in terms of grease rheology.…”
Section: Resultsmentioning
confidence: 99%
“…Radulescu et al [24] investigated the flow in pipes with discontinuities, which also could be applied to the flow in bearings. This work is a continuation of previous studies of the flow in closed straight channels [29,17] and in a 3D double restriction seal geometry [14,1,18]. A channel with a 90 • elbow is used and an analytical model of the flow is developed and combined with experimental data from micro Particle Image Velocimetry (µPIV) measurements of the flow in the elbow.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations